Cell Staining Microgels Derived from a Natural Phenolic Dye: Hematoxylin Has Intriguing Biomedical Potential - Mehtap Sahiner; Aydin K. Sunol; Nurettin Sahiner (MDPI AG, 2024)
Hematoxylin (HT) as a natural phenolic dye compound is generally used together with eosin (E) dye as H&E in the histological staining of tissues. Here, we report for the first time the polymeric particle preparation from HT as poly(Hematoxylin) ((p(HT)) microgels via microemulsion method in a one-step using a benign crosslinker, glycerol diglycidyl ether (GDE). P(HT) microgels are about 10 µm and spherical in shape with a zeta potential value of −34.6 ± 2.8 mV and an isoelectric point (IEP) of pH 1.79. Interestingly, fluorescence properties of HT molecules were retained upon microgel formation, e.g., the fluorescence emission intensity of p(HT) at 343 nm was about 2.8 times less than that of the HT molecule at λex: 300 nm. P(HT) microgels are hydrolytically degradable and can be controlled by using an amount of crosslinker, GDE, e.g., about 40%, 20%, and 10% of p(HT) microgels was degraded in 15 days in aqueous environments for the microgels prepared at 100, 200, and 300% mole ratios of GDE to HT, respectively. Interestingly, HT molecules at 1000 mg/mL showed 22.7 + 0.4% cell viability whereas the p(HT) microgels exhibited a cell viability of 94.3 + 7.2% against fibroblast cells. Furthermore, even at 2000 mg/mL concentrations of HT and p(HT), the inhibition% of α-glucosidase enzyme were measured as 93.2 ± 0.3 and 81.3 ± 6.3%, respectively at a 0.03 unit/mL enzyme concentration, establishing some potential application of p(HT) microgels for neurogenerative diseases. Moreover, p(HT) microgels showed two times higher MBC values than HT molecules, e.g., 5.0 versus 2.5 mg/mL MIC values against Gram-negative E. coli and Gram-positive S. aureus, respectively.